EXPERT SYSTEM FOR DETERMINING IDEAL WEIGHT USING METODE TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) METHODS (International Journal of Psychosocial Rehabilitation, 2020)
Most people do not know their ideal weight. As a result, being overweight becomes a problem that must be solved. Technology has developed rapidly, providing an easy way to do various activities. Using technology, this weight problem can be solved by building a web-based ideal weight calculation application. The method used with the first step of making an application is analyzing system requirements, system design, user interface, coding, and implementation using PHP. The next step is to test the application. With this application, users can easily see changes in toddler weight every month and find out the ideal weight for toddlers. It is hoped that this application can simplify the work of Posyandu employees. This system uses the PHP programming language with a MySQL database and the Technique for Order Preference by Similarity to Ideal Solutions (TOPSIS) method. Functional testing shows that the overall functionality of the system works well.